THE INFLUENCE OF STUDENT’S PERCEPTION ON LEARNING MEDIA AND STUDENT’S MOTIVATION TOWARD STUDENT’S ENGLISH ACHIEVEMENT - Jumroh Jumroh; Oom Rohmah (INFERENCE: Journal of English Language Teaching, 2019)
This study aims to analyze and verify the hypothesis about the influence of students’ perception of learning media and student’s motivation toward student’s English achievement. The hypothesis of the research is 1). There is a significant influence between students’ perceptions and student’s motivation at the same time toward the student’s English achievement. 2). There is a significant influence on students’ perceptions toward student’s English achievement. 3). There is a significant influence of student’s motivation toward student’s English achievement. In this research, researchers used research Analyses regression survey method. The population is from students of Muhammadiyah 2 high school in Tangerang, IT As Syukriyah, and Yuppentek 1 high schools in Tangerang in the 2018/2019 academic year, which completed with 661 students. The sample size of 60 students was chosen randomly from all existing classes with Proportionate Stratified random sampling. The instrument used was a questionnaire. Hypothesis testing results are summarized as follows: (1) There is a significant influence between the student’s perception and student’s motivation on learning media toward student’s English achievement. The result of this research can be implied to improve the quality of English teaching and learning.